2014
DOI: 10.1177/2233865914550727
|View full text |Cite
|
Sign up to set email alerts
|

Cultural intelligence as a predictor of individuals’ adaptive performance: A study in a multicultural environment

Abstract: As the work environment is changing rapidly, organizations need more adaptable employees who can work creatively, learn new skills and adapt to diverse social contexts and novel environments. Individual differences such as prior experience and self-efficacy have been extensively examined as predictors of adaptive performance. In contrast, the role of cultural intelligence in promoting adaptive performance has been overlooked. The primary goal of this study was to examine cultural intelligence that may account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 72 publications
(152 reference statements)
3
19
0
7
Order By: Relevance
“…The findings of this study indicated that CQ provides behavior flexibility, intrinsic interest and adaptability to acquire new in cross cultural setting, represent an important external learning and knowledge acquisition capability (Moon, 2010).Consistent with the previous research the four factors of CQ make unique contributions to effectiveness in culturally diverse settings (Ang, Rockstuhl, & Tan, 2015). The CQ is associated with individual adaptive performance (Sahin & Gürbüz, 2014), this implies that firm contains high level of CQ inclined towards high adaption to the partner requirements and utilize these adapted knowledge for improvement in social performance. The findings of this study provide a contribution and support the logic of organizational culture inevitable for the sustainable growth of firm (Awan, Muneer, & Abbas, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The findings of this study indicated that CQ provides behavior flexibility, intrinsic interest and adaptability to acquire new in cross cultural setting, represent an important external learning and knowledge acquisition capability (Moon, 2010).Consistent with the previous research the four factors of CQ make unique contributions to effectiveness in culturally diverse settings (Ang, Rockstuhl, & Tan, 2015). The CQ is associated with individual adaptive performance (Sahin & Gürbüz, 2014), this implies that firm contains high level of CQ inclined towards high adaption to the partner requirements and utilize these adapted knowledge for improvement in social performance. The findings of this study provide a contribution and support the logic of organizational culture inevitable for the sustainable growth of firm (Awan, Muneer, & Abbas, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Görev performansı (Presbitero, 2016a;Şahin & Gürbüz, 2012), iş performansı (Wang, 2016), lider performansı, takım performansı (Groves & Feyerherm, 2011) (Moon vd. ,2012), dil yeteneği ve yurtdışı çalışma niyeti (Remhof, Gunkel & Schlägel 2013), kültürel psikolojik sermaye ve üst bilişsel farkındalık (Remhof, Gunkel & Schlägel, 2014), bireysel uyarlanabilir performans ve öz-yeterlilik/geçmiş deneyim, deneyime açıklık ve iş doyumu (Şahin & Gürbüz, 2014), çok kültürlülük ve yaratıcı iş davranışı (Korzilius, Bücker & Beerlage, 2017), dil yeteneği ve görev perfromansı (Presbitero, 2017), uluslararası seyahat deneyimi/kültürlerarası sosyal iletişim ve göçmenlik isteği (Lee, Webera, Rivera, 2019) arasındaki ilişkide pozitif yönlü, tamamen aracılık rolü üstlenmektedir (Bkz. Tablo 6).…”
Section: Kültürel Zekâ: Doğrudan Etkisiunclassified
“…Ancak, Aracı Etki Yöntemi ile incelenen araştırmaların sayısının oldukça az olduğu gözlenmektedir (12). Öyle ki, KZ konusu, yerli literatürde aracılık modeli ile yalnızca 1 çalışmada yer almıştır (Şahin & Gürbüz, 2014).…”
Section: Sonuç Ve öNeri̇lerunclassified
“…Ayrıca küreselleşme, teknolojik gelişmeler ve yapılan işlerde meydana gelen değişiklikler de işgörenlerin çalışma ortamlarında yeni ve farklı durumlara uyum sağlamalarını gerektirmektedir. Günümüz örgütlerinde meydana gelen bu önemli değişiklikler nedeniyle uyumsal performans çalışma ortamlarında gittikçe önem kazanmakta (Pulakos ve diğerleri, 2000) ve son zamanlarda birçok farklı alandaki araştırmalara (Allworth ve Hesketh, 1999;Baard ve diğerleri, 2014;Bhat ve Beri, 2016;Calarco, 2016;Charbonnier-Voirin, El Akremi ve Vandenberghe, 2010;Charbonnier-Voirin ve Roussel, 2012;Griffin ve Hesketh, 2003;Griffin ve Hesketh 2004;Griffin ve Hesketh, 2005;Griffin, Parker ve Mason, 2010;Han ve William, 2008;Huang, Ryan, Zabel ve Palmer, 2014;Jundt, Shoss ve Huang, 2014;LePine, Colquitt ve Erez, 2000;Lillard, Watts, Frame, Hein, Rigdon ve Orsak-Robinson, 2012;Marlow, 2016;Marlow, Calarco, Frame ve Hein, 2015;Neal, Yeo, Koy ve Xiao, 2012;Ployhart ve Bliese, 2006;Pulakos ve diğerleri, 2000;Pulakos, Schmitt, Dorsey, Arad, Borman ve Hedge, 2002;Samale, 2016;Schrub, Stegmaier ve Sonntag, 2011;Seyfang, Frame, Jackson ve Hein, 2017;Shoss, Witt ve Vera, 2012;Stokes, Schneider ve Lyons, 2010;Şahin ve Gürbüz, 2014;Tucker, Gunther, Pleban, Goodwin ve Vaughan 2007;White, Mueller-Hanson, Dorsey, Pulakos, Wisecarver, Deagle ve Medini, 2005;Zorzie, 2012) konu olmaktadır.…”
Section: Uyumsal Performansunclassified